Quantitative and qualitative evaluation of esquiterpenoids from essential oil and in vitro somatic embryos of east Indian Sandalwood (Santalum album) tree by HPTLC and GC (Open Access Journal of Medicinal and Aromatic Plants, 2013)
Sandalwood finds numerous applications in Ayurveda. The bioactive and fragrant constituents of the essential oil are sesquiterpenoid alcohols known as santalols. Typically, GC and GC-MS have been used to analyze santalols. However, there are no HPTLC-based methods available. Hence, we evaluated the sesquiterpenoids from sandalwood oil by means of an HPTLC method. Using a standard curve based on á-santalol (y=684.8x +5970, r2= 0.887), the sesquiterpenoids were quantified by HPTLC. Furthermore, solvent extracts of in vitro grown somatic embryos were analyzed for the first time to quantify sesquiterpenoids. The results obtained from HPTLC were compared against that of GC. We found out that, GC and HPTLC analyses could resolve 16 and 9 major constituents of sandalwood oil, respectively. Besides, the sesquiterpenoid content in somatic embryos was 55.75 ± 12.36 ng g-1 FW. The sesquiterpenoid alcohol content of sandalwood oil was 2.5 folds higher than somatic embryo. Furthermore, we showed that by using HPTLC derived spectral scans at 208 nm as fingerprints of á- and â- santalols, it could be helpful in identification of the constituents. We conclude that an HPTLC based analysis method allows routine identification of sesquiterpenoids. Additionally, the somatic embryos hold potential as an alternative bioresource for obtaining sesquiterpenoid constituents present in sandalwood oil.